2021
DOI: 10.1057/s41599-021-00710-3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of social isolation on well-being and life satisfaction during pandemic

Abstract: The SARS-CoV-2 pandemic placed many locations under ‘stay at home” orders and adults simultaneously underwent a form of social isolation that is unprecedented in the modern world. Perceived social isolation can have a significant effect on health and well-being. Further, one can live with others and still experience perceived social isolation. However, there is limited research on psychological well-being during a pandemic. In addition, much of the research is limited to older adult samples. This study examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
152
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(193 citation statements)
references
References 31 publications
(57 reference statements)
6
152
0
5
Order By: Relevance
“…This study found that younger adults (aged 18-29 years) reported higher self-isolation than older groups. Those feeling socially isolated were also less satisfied with their food habits, work, and housing 215 . Prolonged social media use has had a deleterious effect on the overall social well being of individuals as reported by studies in Saudi Arabia 212 and Italy 216 .…”
Section: Emotional Wellbeing and Social Connectednessmentioning
confidence: 99%
“…This study found that younger adults (aged 18-29 years) reported higher self-isolation than older groups. Those feeling socially isolated were also less satisfied with their food habits, work, and housing 215 . Prolonged social media use has had a deleterious effect on the overall social well being of individuals as reported by studies in Saudi Arabia 212 and Italy 216 .…”
Section: Emotional Wellbeing and Social Connectednessmentioning
confidence: 99%
“…When people cannot get rested and recover from work, they are more likely to feel depressed and emotionally exhausted (Dunford et al, 2012;Bliese et al, 2017). When people stay at home for a long time, they are also likely to generate negative emotions and experience "cabin fever" (Clair et al, 2021). From a cognitive perspective, people make a large number of decisions every day.…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
“…Therefore, focusing energy on preventing the vast majority of infections that occur indoors, 2 15 while allowing the outdoors to be a place where people's energy is recharged through fresh air, physical activity, and social connection, would pay great dividends from a public health perspective. 24 Equity concerns are also vital, because people who have access to back gardens or can afford private transport to less population dense areas can enjoy the outdoors unmasked. In contrast, many others without such privileges or resources cannot enjoy fresh air or exercise unmasked in settings where mask use is universally mandated outdoors.…”
Section: User Costsmentioning
confidence: 99%
“…It might also result in some people gathering indoors or refraining from exercise, a crucial component of mental and physical health. Therefore, focusing energy on preventing the vast majority of infections that occur indoors,215 while allowing the outdoors to be a place where people’s energy is recharged through fresh air, physical activity, and social connection, would pay great dividends from a public health perspective 24…”
Section: No—muge Cevik Zeynep Tufekci Stefan Baralmentioning
confidence: 99%